Improving Students’ Reading Skills in Understanding English Texts Using Culture-Based Text Teaching Materials - Yon Adlis; Robi Soma; Sufri Sufri (Universitas Pahlawan Tuanku Tambusai, 2022)
One of the factors causing the lack of success in reading comprehension in English in high school is the text used in learning that is set in a foreign culture. This study aims to describe the improvement of students' skills in understanding the contents of reading texts by using a model of text-based teaching materials based on local culture. This research uses classroom action research with implementation steps; (1) initial observations to determine research problems and data collection; (2) formulate research action plans, formulate models of teaching materials (3) development of teaching materials; (4) carry out the action; (5) collaborate with English teachers; (6) draw up a teaching plan; (7) reflection and revision of actions; (8) classroom action; (9) improvement of teaching materials. The subjects of this study were two English teachers and 28 high school students in class XI who were studying English with the topic of Reading Comprehension. The results showed an increase in student involvement in discussions, higher student initiative to ask questions, higher student activity in digging information. Learning outcomes indicated by the level of students' ability to answer questions are also getting higher. Learning becomes more effective and efficient in achieving learning objectives.